MGS Guaiçara and MGS Vereda: Coffea arabica cultivars resistant to the root-knot nematode meloidogyne paranaenses. - SALGADO, S. M. de L. (2022)
MGS Guaiçara e MGS Vereda are resistant to Meloidogyne paranaensis, one of the most aggressive nematode parasites of coffee. MGS Vereda is an early maturation cultivar, whereas MGS Guaiçara has a medium maturation cycle. Both cultivars produce red fruit, have high size, and high yield potential in infested areas.